Degradation of BDE-47 in mangrove sediments with amendment of extra carbon sources. (April 2020) - Pan, Ying; Chen, Juan; Zhou, Haichao; Cheung, S.G.; Tam, Nora F.Y.
Abstract: Polybrominated diphenyl ethers (PBDEs) are widely detected in coastal wetlands but their remediation is still difficult. In this study, different carbon sources, namely formate, acetate, pyruvate, lactate, succinate, methanol and ethanol, were added to mangrove sediments contaminated with BDE-47, a common PBDE congener, to enhance its degradation. After 2-month incubation, all carbon addition significantly enhanced degradation percentages. The residual BDE-47 percentage significantly correlated with the abundance of total bacteria and Dehalococcoides spp. The addition of methanol, acetate and succinate also achieved significantly higher degradation rates and shorter half-lives than sediments without carbon amendment at the end of 5-month incubation, although degradation percentages were comparable between sediments with and without extra carbon. The degradation pathway based on the profiles of degradation products was also similar among treatments. The results indicated the stimulatory effect of extra carbon sources on BDE-47 degradation in contaminated sediments was carbon- and time-specific. Highlights: All carbon addition enhanced degradation of BDE-47 in mangrove slurries at month 2. Methanol, succinate and acetate also accelerated BDE-47 degradation rates. Degradation percentage correlated with Dehalococcoides spp.' abundance at month 2. But final degradation percentage at month 5 was not improved by any carbon source.